Right transradial coronary angiography in the setting of tortuous brachiocephalic/thoracic aorta ("elephant head"): Impact on fluoroscopy time and contrast use. Issue 2 (25th January 2021) - Case, Brian C.; Yerasi, Charan; Forrestal, Brian J.; Chezar‐Azerrad, Chava; Khan, Jaffar M.; Khalid, Nauman; Shlofmitz, Evan; Chen, Yuefeng; Musallam, Anees; Waksman, Ron; Hashim, Hayder
Abstract: Objectives: Assess the impact on fluoroscopy time and contrast use in patients with tortuous brachiocephalic/thoracic aortas undergoing right transradial coronary angiography (RTCA) and provide strategies to manage. Background: Unfavorable anatomy with severe brachiocephalic/thoracic tortuosity, referred to as an "elephant head, " remains a significant obstacle for RTCA. Methods: We reviewed the coronary angiograms of patients who underwent RTCA and had tortuous aortas. Angiography was attempted first using a universal catheter (Tiger) and switched to a left coronary specific catheter (Judkins Left [JL]) if challenging. Fluoroscopy time, contrast volume, and greatest distance from the patient's midline to the catheter in the aorta were recorded. Results: Forty‐nine patients (62.6 ± 12.0 years, 69.4% male) were included. Fifteen (30.6%) patients underwent successful angiography with a Tiger catheter; 34 (69.4%) patients required switching to JL catheter. The average distance of Tiger catheters to the midline of the spine was 0.78 ± 0.41 cm versus 1.28 ± 0.44 cm ( p = .001) in JL catheters. Tiger catheter use resulted in less fluoroscopy time (6.48 ± 4.73 min) and contrast use (58.87 ± 43.53 ml) than in cases switched to JL (13.26 ± 10.76 min [ p = .026]; 86.5 ± 69.95 ml [( p = .017]). Conclusions: For patients undergoing RTCA with significant brachiocephalic/thoracic aorta tortuosity, "elephant head, " a Tiger catheter can be used efficiently for curvatures <1 cm from the middle of the spine. We propose that for curvatures >1 cm, operators should consider immediately switching to a JL catheter.